IMPLEMENTASI PENDIDIKAN KARAKTER BANGSA PADA PEMBELAJARAN MATEMATIKA SMPN 5 BATUSANGKAR - Dona Afriyani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
Goverment will about the implementation of character education needs for appropriateness of ‘Kurikulum Tingkat Satuan Pendidikan’ (KTSP) in form of modification of learning tools at all subjects. Mathematics as one of many general subjects, for example, needs to integrate character values in order to have good characters. Therefore, it is better to explore preparation, implementation, evaluation, and all teachers’ difficulties in implementing character education in teaching Math at junior high school. Through descriptive qualitative research, this study had been successful to show a fact about the information that was relevant with the implementation.Kata kunci: pendidikan karakter, pembelajaran matematika